2022
DOI: 10.3389/fnins.2022.882316
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes in Neurodegeneration: Inspiration From Genetics

Abstract: Despite the discovery of numerous molecules and pathologies, the pathophysiology of various neurodegenerative diseases remains unknown. Genetics participates in the pathogenesis of neurodegeneration. Neural dysfunction, which is thought to be a cell-autonomous mechanism, is insufficient to explain the development of neurodegenerative disease, implying that other cells surrounding or related to neurons, such as glial cells, are involved in the pathogenesis. As the primary component of glial cells, astrocytes pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 182 publications
(196 reference statements)
3
6
0
Order By: Relevance
“…Thus, our ability to generate mixed GRN +/+ neurons + GRN -/astrocytes showing nearly as strong crSTMN2 and TDP-43 phenotypes of full GRN -/neuron and astrocyte cultures indicate that GRN loss of function in human astrocytes can lead to TDP-43 loss of function in neurons. This finding is mechanistically important and adds to a growing body of literature suggesting that disease associated astrocytes and more generally glia can drive cell death and neuronal dysfunction (Huang et al, 2022;Leng et al, 2021;Liddelow et al, 2017;Taha et al, 2022;Zhang et al, 2020) Our investigation of phagocytic activity assay in GRN -/ -iAstrocytes demonstrated significant deficit when compared to GRN +/+ iAstrocytes. Phagocytic changes have been reported in GRN -/microglia (Guan et al, 2020; and in microglia differentiated from ALS peripheral blood mononuclear cells (PBMCs) when compared to control PBMCs-derived microglia (Quek et al, 2022).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Thus, our ability to generate mixed GRN +/+ neurons + GRN -/astrocytes showing nearly as strong crSTMN2 and TDP-43 phenotypes of full GRN -/neuron and astrocyte cultures indicate that GRN loss of function in human astrocytes can lead to TDP-43 loss of function in neurons. This finding is mechanistically important and adds to a growing body of literature suggesting that disease associated astrocytes and more generally glia can drive cell death and neuronal dysfunction (Huang et al, 2022;Leng et al, 2021;Liddelow et al, 2017;Taha et al, 2022;Zhang et al, 2020) Our investigation of phagocytic activity assay in GRN -/ -iAstrocytes demonstrated significant deficit when compared to GRN +/+ iAstrocytes. Phagocytic changes have been reported in GRN -/microglia (Guan et al, 2020; and in microglia differentiated from ALS peripheral blood mononuclear cells (PBMCs) when compared to control PBMCs-derived microglia (Quek et al, 2022).…”
Section: Discussionsupporting
confidence: 60%
“…Thus, our ability to generate mixed GRN +/+ neurons + GRN −/− astrocytes showing nearly as strong crSTMN2 and TDP-43 phenotypes of full GRN −/− neuron and astrocyte cultures indicate that GRN loss of function in human astrocytes can lead to TDP-43 loss of function in neurons. This finding is mechanistically important and adds to a growing body of literature suggesting that disease associated astrocytes and more generally glia can drive cell death and neuronal dysfunction (Huang et al, 2022; Leng et al, 2021; Liddelow et al, 2017; Taha et al, 2022; Zhang et al, 2020)…”
Section: Discussionsupporting
confidence: 53%
“…Thus, our ability to generate mixed GRN +/+ neurons + GRN −/− astrocytes showing nearly as strong crSTMN2 and TDP-43 phenotypes of full GRN −/− neuron and astrocyte cultures indicate that GRN LoF in human astrocytes can lead to TDP-43 LoF in neurons. This finding is mechanistically important and adds to a growing body of literature suggesting that disease-associated astrocytes and more generally glia can drive cell death and neuronal dysfunction ( Huang et al., 2022 ; Leng et al, 2022 ; Liddelow et al., 2017 ; Taha et al., 2022 ; Zhang et al., 2020 ).…”
Section: Discussionsupporting
confidence: 53%
“…On the other hand, glial cells may perform neurotoxic roles via the production of pro-inflammatory cytokines or ROS ( Figure 3 ). Activated glia may perform neuroprotective or neurotoxic roles depending on the stage of PD and the conditions of glial cells such as the ROS level [ 277 , 278 , 279 , 280 ]. Accordingly, activated microglia and astrocyte are neuroprotective in the initial stage of PD, but become neurotoxic to promote neurodegeneration in a later stage [ 43 , 279 ].…”
Section: Feedback Of Glial Activation On Da Neuron Degenerationmentioning
confidence: 99%
“…It is speculated that activated microglia and astrocyte may be initially non-toxic and neuroprotective by producing trophic factors, neurotrophins, and antioxidant substances. However, in the later stage they become neurotoxic owing to a toxic change caused by other factors such as long-term α-syn stress, toxic substances, viruses, or inflammatory cells that might occur to promote PD progression [ 277 , 279 , 280 ].…”
Section: Feedback Of Glial Activation On Da Neuron Degenerationmentioning
confidence: 99%